ISSUES OF ORGANIZATION OF MANAGEMENT ACCOUNTING AT THE ENTERPRISE - Khamidova S.Y. (Scholar Express Journals, 2023)
The paper deals with the application of modern methods of cost management in the organization of management accounting at the enterprise.
Keywords: Costs; management accounting; management analysis